2019
DOI: 10.1002/andp.201900014
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Measurement's Uncertainty in the Curved Space‐Time

Abstract: The dynamical characteristics of measurement's uncertainty are investigated under two modes of Dirac field in the Garfinkle-Horowitz-Strominger dilation space-time. It shows that the Hawking effect induced by the thermal field would result in an expansion of the entropic uncertainty with increasing dilation-parameter value, as the systemic quantum coherence reduces, reflecting that the Hawking effect could undermine the systemic coherence. Meanwhile, the intrinsic relationship between the uncertainty and quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 82 publications
(76 reference statements)
0
12
1
Order By: Relevance
“…In quantum information theory, the uncertainty principle is popularly formulized in terms of entropy. The effects of Hawking radiation on the entropic uncertainty in a Schwarzschild space-time are analyzed in [6] and the relationship between the entropic uncertainty and quantum coherence is obtained in [7]. Finally in [8] an improvement of the tripartite quantum-memory-assisted entropic uncertainty relation is obtained.…”
Section: ( )mentioning
confidence: 99%
“…In quantum information theory, the uncertainty principle is popularly formulized in terms of entropy. The effects of Hawking radiation on the entropic uncertainty in a Schwarzschild space-time are analyzed in [6] and the relationship between the entropic uncertainty and quantum coherence is obtained in [7]. Finally in [8] an improvement of the tripartite quantum-memory-assisted entropic uncertainty relation is obtained.…”
Section: ( )mentioning
confidence: 99%
“…Moreover, the quantum‐memory‐assisted EUR for the Dirac particles in the background of a Garfinkle–Horowitz–Strominger (GHS) dilation black hole have been studied . Generally, the spherically symmetric line element of another black hole (GHS dilation space‐time) can be given by truerightds2=leftr()r2D()dθ2+sin2θdϕ2()r2Mr2Ddt2left+0.16emr2Mr2D1dr2where M and D denote parameters with respect to the mass of black hole and dilation field, respectively.…”
Section: The Dynamical Uncertainty In Open Systems and Its Manipulationmentioning
confidence: 99%
“…Moreover, the quantum-memory-assisted EUR for the Dirac particles in the background of a Garfinkle-Horowitz-Strominger (GHS) dilation black hole have been studied [83,84]. Generally, the spherically symmetric line element of another black hole (GHS dilation space-time) can be given by…”
Section: Dynamics Of the Eur In Specific Systems A The Curved Space-timementioning
confidence: 99%
“…Understanding quantum effects in the framework of relativity [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] is essential. For example, it was found that nonclassical correlations are generated between the open charts in the exponentially expanding de Sitter space [36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%